Penguatan Pendidikan Islam di Era Teknologi - Kholis, Nur; Luluk Istiarohmi; Cahyani, Dita Dwi (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
This study aims to explain the role of Islamic education in overcoming various educational problems in the technological era. In essence, education has a very large impact on the progress of human civilization. With education, students are equipped to face challenges in the future. Along with the times, technology is developing rapidly, including artificial intelligence, Islamic education is able to show its existence. This study uses qualitative research with literature studies. The stages carried out in this study were data reduction, data presentation, and drawing conclusions. The results of this study are that Islamic education needs to be continuously improved so that it can provide proportional implications according to the times. Islamic education combines scientific values both intellectually and spiritually. This can be used as a solution to overcome various problems faced in the world of education in the technological era.